2022
DOI: 10.1002/cft2.20142
|View full text |Cite
|
Sign up to set email alerts
|

Corn productivity and profitability in raised stale seedbed systems with and without cover crops

Abstract: Cover crops are promoted for reducing the negative environmental effects of high‐input row‐crop production; however, cover crop adoption in the mid‐southern United States is low, partly because of a perceived increase in risk. The objective of this research was to determine if cover crops cost‐effectively improved the productivity and water use of corn (Zea mays L.) in raised stale seedbed systems. The effects of four cover crops, namely Austrian winter pea [Pisum sativum var. arvense (L.) Poiret], crimson clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The previous winter pea treatment in Spencer et al. (2021) did not improve maize yield during any year from 2017 to 2020, so the subsequent PAM treatment in the present study is unlikely to have inherited any hidden advantages. For 2022 in the present study, the first PAM application occurred shortly before intense rainfall, and maize yield was not significantly different between PAM and CT. Perhaps the timing and method of PAM application can alter its impact on crop yield.…”
Section: Resultsmentioning
confidence: 46%
See 4 more Smart Citations
“…The previous winter pea treatment in Spencer et al. (2021) did not improve maize yield during any year from 2017 to 2020, so the subsequent PAM treatment in the present study is unlikely to have inherited any hidden advantages. For 2022 in the present study, the first PAM application occurred shortly before intense rainfall, and maize yield was not significantly different between PAM and CT. Perhaps the timing and method of PAM application can alter its impact on crop yield.…”
Section: Resultsmentioning
confidence: 46%
“…Wesley (1998) discussed the challenges in an NT system, which requires more attention to increased weed pressure due to the absence of tillage. Spencer et al (2021) found that cover crops grown in a subhumid climate did not boost maize yield in any of the 4 years of the study. This may be attributed to nitrogen (N) availability issues, seed-bed conditions, and fast cover crop decomposition due to early termination.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations